Patient experience of non-conveyance in the EMS of Southwest Finland: a descriptive survey study - Skaffari, Eetu (BioMed Central Ltd, 2025)
Background: Emergency Medical Services are dispatched more frequently than before. However, many non-urgent patients do not need ambulance transportation to a healthcare facility after evaluation and treatment on scene. This study explored the experiences of non-conveyed patients. Our research questions were: (1) How have non-conveyed patients experienced the service received from EMS? (2) Does a patient's age, gender, or time of the emergency call impact the patient's experience?
Methods: This descriptive survey study examined non-conveyed Emergency Medical Services patients in the Wellbeing Services County of Southwest Finland. The study period was from March 1, 2023, to March 31, 2023. The study population was 1017. They received a questionnaire that was sent by mail. The questionnaire was formed based on questions previously used in four different questionnaires. We received 247 answers (24.3% response rate). Percentages, medians with interquartile ranges, and non-parametric tests were used in the descriptive analyses.
Results: Non-conveyed patients were very satisfied with the paramedics' expertise and behavior, their ability to meet their individual needs, the sense of safety provided by the paramedics, and the instructions given to the patients. Time to receive help (19% rated 3 or less on a scale from 1 to 5), how paramedics introduced themselves (16.5%), and satisfaction with non-conveyance decisions (14.6%) were more frequently rated lower than other areas. Further, pain management stood out in the less favorable evaluations. Still, patients' experiences of the service were positive. The age group, gender, or time of the emergency call were not associated with patient experience.
Conclusions: Patients were very satisfied with the paramedics' interpersonal skills. A more focused approach to pain management and developing EMS to ensure faster patient outreach and clearer explanations of non-conveyance decisions could further enhance the patient experience.